Plant Extract Mediated Green Synthesis of Selenium Nanoparticle and Its Antimicrobial Activity: A Brief Review - Rajesh Dev Sarkar; Jutika Deka; Mohan Chandra Kalita (Innovations in Microbiology and Biotechnology Vol. 2, 2021)
The use of nanotechnology in biological fields have gained tremendous attention in recent times with their application in fields like cancer therapy, drug delivery, biosensors, antioxidant, anti-microbial, agriculture etc. Gold, silver, iron, copper, nickel and selenium for their excellent biological activity are the most commonly synthesized nanoparticles, of which selenium nanoparticles will be the main focus of this review. Green synthesis of SeNPs is an environmentally safer option than other methods. Based on the raw materials and the techniques used, selenium nanoparticles of various shapes and sizes can be fabricated which imparts specific properties to each form of nanoparticles produced. Plant samples such as Aloe vera leaves, citrus fruits and cinnamon bark having known bio-active properties are found suitable for green synthesis of selenium nanoparticles. The advantages of using selenium are its availability in nature, lower toxicity (in its nanoparticle form) and its antimicrobial and antioxidant properties. The combined effect of the plant’s bioactive properties, selenium’s antioxidant properties and increased reactivity in nano-particle form have worked wonders against some of the harmful human pathogens even though the exact mode of action is not known. With the growing resistance of microbial pathogens against the current arsenal of antibiotics, these modern approaches are the need of the highest order in our fight against microbial infections. Here in this review, green synthesis of Selenium nanoparticles using different plant extracts, their characterization techniques and the antimicrobial activity against several bacteria and fungi have been discussed.